Behavioral anxiolysis without reduction of hippocampal theta frequency after histamine application in the lateral septum of rats. Issue 6 (28th January 2014) - Chee, San‐San A.; Menard, Janet L.; Dringenberg, Hans C.
ABSTRACT Hippocampal theta activity is linked to various processes, including locomotion, learning and memory, and defense and affect (i.e., fear and anxiety). Interestingly, all classes of clinically effective anxiolytics, as well as experimental compounds that decrease anxiety in pre‐clinical animal models of anxiety, reduce the frequency of hippocampal theta activity elicited by stimulation of the reticular formation in freely behaving or anesthetized animals. In the present experiments, we found that bilateral histamine infusions (0.5 µg/hemisphere) into the lateral septum (LS) of rats decreased anxiety‐like responses in two models of anxiety, the elevated plus maze and novelty‐induced suppression of feeding test. Surprisingly, these same infusions significantly increased hippocampal theta frequency elicited by reticular stimulation in urethane‐anesthetized rats. In contrast to these findings, additional experiments showed that the clinically effective anxiolytic buspirone (40 mg/kg, i.p.) reduced theta frequency, confirming previous observations. Taken together, the dissociation of behavioral anxiolysis and theta frequency reduction noted here suggest that hippocampal theta frequency is not a direct index of anxiety levels in rodents. Further, the mechanisms underlying the behavioral and physiological effects elicited by histamine in the LS require further study. © 2014 Wiley Periodicals, Inc.